Hubungan Motif Penggunaan dan Tingkat Pemenuhan Kebutuhan Informasi Bagi Followers Aktif @beeruindonesia - Gladys Tampubolon; Uud Wahyudin; Setiaman, Agus (CV. Creative Tugu Pena, 2024)
Almost all people in the world cannot be separated from the internet. Various information can be obtained and disseminated through the internet. @beeruindonesia is a healthy living service platform that markets products and disseminates information online. Among other things, @beeruindonesia disseminates information about healthy eating through the Instagram account @beeruindonesia. Using Uses and Gratifications Theory with the concept of MAIN (modality, agency, interactivity, navigability), this study aims to (i) measure the motives for using the @beeruindonesia Instagram account in each of the four dimensions, (ii) measure the fulfillment of information needs of active followers of the @beeruindonesia Instagram account and (iii) analyze the relationship (correlation) between motives (in general and each dimension) with the fulfillment of information needs of followers of the @beeruindonesia Instagram account. The research method approach is a combination of qualitative and quantitative research methods. This study concludes that (i) the motives for using the @beeruindonesia Instagram account based on modality, agency, interactivity, and navigability are very high, (ii) the level of fulfillment of information needs is very high, and (iii) the motives for using the @beeruindonesia Instagram account both partially and combined are positively and strongly correlated with the need to fulfill information for followers of the @beeruindonesia Instagram account. The positive and strong correlation is significant at the 99% confidence level (α = 0.01)